2013
DOI: 10.1007/s10266-013-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air polishing on the resin composite–dentin interface

Abstract: The aim of this study was to examine defect depths and volumes at the resin composite-dentin (R/D) interface after air polishing with different particles and spray angles. Samples were 54 dentin specimens that were formed in saucer-shaped cavities filled with resin composite. Each specimen was air polished with either sodium bicarbonate (NaHCO3) or one of two glycine (Gly) powders. The air polisher was set at angles of 90° to the interface and at 45° to the interface from both the dentin and resin composite si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
8
0
3
Order By: Relevance
“…Air-power polishers are available with a broad range of powders. When selecting a powder, two aspects have to be weighed: the effectiveness desired from the cleaning, and surface abrasion [24]. A powder characterized by greater abrasiveness removes both undesirable and desirable tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Air-power polishers are available with a broad range of powders. When selecting a powder, two aspects have to be weighed: the effectiveness desired from the cleaning, and surface abrasion [24]. A powder characterized by greater abrasiveness removes both undesirable and desirable tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine powders have a lower hardness than sodium bicarbonate powders, and cause less damage to the dentin surface and the gingival epithelium [22][23][24][25] . In addition, glycine powders produced smaller changes in dentin surface parameters than sodium bicarbonate powders 23,26) . Therefore, air-flow powder SOFT was used to remove the temporary sealing material.…”
Section: Discussionmentioning
confidence: 88%
“…Acids with different concentrations and types have been used in studies and various result have been obtained. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Surface treatment with acid alone did not produce remarkable changes in the superficial texture of the composite compared with that of an untreated sample; it seemed to only have a cleaning effect. 29 In the present study, acid etching of the surface increased the bond strength of the aged composite.…”
Section: Discussionmentioning
confidence: 90%
“…Shimizu et al 36 reported that air polishing causes increasing the surface roughness of the composite. In a previous study, Rinaudo et al 37 concluded that air polishing cannot remove the smear layer; therefore, the bond strength of the restorations decreases.…”
Section: Discussionmentioning
confidence: 99%